Dealing with financial instability under a DSGE modeling approach with banking intermediation: A predictability analysis versus TVP-VARs - Stelios Bekiros; Roberta Cardani; Alessia Paccagnini; Stefania Villa (University College Dublin, UCD School of Economics, 2016)
In the dynamic stochastic general equilibrium (DSGE) literature there has been an increasing aware- ness on the role that the banking sector can play in macroeconomic activity. We present a DSGE model with financial intermediation as in Gertler and Karadi (2011). The estimation of shocks and of the structural parameters shows that time-variation should be crucial in any attempted empirical analysis. Since DSGE modelling usually fails to take into account inherent nonlinearities of the economy, we propose a novel time-varying parameter (TVP) state-space estimation method for VAR processes both for homoskedastic and heteroskedastic error structures. We conduct an exhaustive empirical exercise to compare the out-of-sample predictive performance of the estimated DSGE model with that of standard ARs, VARs, Bayesian VARs and TVP-VARs. We find that the TVP-VAR provides the best forecasting performance for the series of GDP and net worth of financial intermediaries for all steps-ahead, while the DSGE model outperforms the other specifications in forecasting inflation and the federal funds rate at shorter horizons.
Keywords: C11; C13; C32; E37; 330; Financial frictions; DSGE; Time-varying coefficients; Extended Kalman filter; Banking sector